Mempersuasi Dan Menumbuhkan Motivasi Siswa Untuk Melanjutkan Pendidikan Ke Tingkat Perguruan Tinggi - Alfiyaty, Rizqy; Adrian, Donal; Fadhliah, Fadhliah; Yusaputra, Muhammad Isa; Mahardika, I Putu Agus Eka Jaya; Asiyah, Rihadatul; Samsiar, Samsiar; Rahma, Syafina Aulia (Journal Of Human And Education (JAHE), 2024)
Every Indonesian citizen has the right to receive education up to university level. The right to receive education is one of the human rights stated in CHAPTER XIII on Education and Culture in the 1945 Constitution after the amendment, namely Article 28 paragraph (1) which states "everyone has the right to develop themselves through the fulfillment of their basic needs, has the right to receive education and obtain benefits from science and technology, art and culture, in order to improve their quality of life and for the welfare of humanity". Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have spiritual religious strength, self-control, personality, intelligence, noble morals, and the skills needed by themselves, society, nation and state (Law No. 20 of 2003). Based on the reality, many students in grade XII of high school or equivalent are found to no longer continue their education in college for economic reasons, family support factors, and others. In fact, the main goal in continuing education to college level is to be able to improve the quality of human resources, change life for the better, be useful for anyone and be able to get a job to meet their life needs. In this service, the author focuses on students of SMA Negeri 7 Palu to be able to persuade and motivate them to have the enthusiasm to continue their education to undergraduate level.